Analisis Faktor Yang Berhubungan dengan Kejadian Diare di Desa Babai Kalimantan Tengah - Diana Pefbrianti; Sri Astuti (Journal of Bionursing, 2021)
ABSTRACT Background. Environmentally based diseases still dominate health problems in developing countries this can occur because of the interactive relationship between humans and their behavior and environmental components that have the potential for diseases such as diarrhea. Many risk factors are suspected to cause diarrheal diseases, including poor environmental sanitation, unattended water supplies, lack of knowledge. In addition, individual hygiene factors that are not good and do not have their own latrines etc. can cause diarrhea too. The purpose of this study is to find out factors related to diarrhea events in babai village in central Kalimantan. Methods. A deskriptif analitik study was conducted. Totally, 81 respondents lived in Babai village Central Kalimantan were invited to contribute. The sample was collected by purposive sampling technique. Questioners were utilized, included knowledge, behaviour, commitment and environmental sanitation. Spearman rho test were applied to describe the data. Results. Mosts of respondents are in less knowledge as 39 respondents (48,1%), Mosts of respondents have a negative commitment in median score behaviour as 41 respondents (50,6%), Mosts of respondents have a negative commitment as 52 respondents (64,2,1%), Mosts of respondents are in median score of environment sanitation as 46 respondents (56,8%). Data analysis obtained p=0.000 in all factors related. Results showed that the knowledge, behaviour, commitment and environment sanitation are related to diarrhea in Babai village central Kalimantan. Conclusion. Results showed that the knowledge, behaviour, commitment and environment sanitation are related to diarrhea in Babai village central Kalimantan.